Neurostructural abnormalities in pediatric anxiety disorders. (May 2015) - Strawn, Jeffrey R.; Hamm, Lisa; Fitzgerald, Daniel A.; Fitzgerald, Kate D.; Monk, Christopher S.; Phan, K. Luan
Highlights: The neuroanatomy of fear and threat processing systems in youth is largely unknown. Neurostructural studies of pediatric anxiety may improve risk detection. Anterior cingulate gray matter volumes are increased in anxious youth. In anxious youth, gray matter volumes in the inferior frontal gyrus, cuneus/precuneus and amygdala are decreased. Abstract: Functional neuroimaging studies have consistently demonstrated abnormalities in fear and threat processing systems in youth with anxiety disorders; however, the structural neuroanatomy of these systems in children and adolescents remains largely unknown. Using voxel-based morphometry (VBM), gray matter volumes were compared between 38 medication-free patients with anxiety disorders (generalized anxiety disorder; social phobia; separation anxiety disorder, mean age: 14.4 ± 3 years) and 27 comparison subjects (mean age: 14.8 ± 4 years). Compared to healthy subjects, youth with anxiety disorders had larger gray matter volumes in the dorsal anterior cingulate and had decreased gray matter volumes in the inferior frontal gyrus (ventrolateral prefrontal cortex), postcentral gyrus, and cuneus/precuneus. These data suggest the presence of structural differences in regions previously implicated in the processing and regulation of fear in pediatric patients with anxiety disorders.